Renal Programming by Transient Postnatal Overfeeding: The Role of Senescence Pathways - Juvet, Christian; Siddeek, Benazir; Yzydorczyk, Catherine; Vergely, Catherine; Nardou, Katya; Armengaud, Jean-Baptiste; Benahmed, Mohamed; Simeoni, Umberto; Cachat, François; Chehade, Hassib (Frontiers in Physiology, 2020)
Background: Early nutrition influences the risk of Chronic Kidney Diseases development in adulthood. Mechanisms underlying the early programming of altered renal function remain incompletely understood. This study aims at characterizing the role of cell senescence pathways in early programming of Chronic Kidney Disease after transient postnatal overfeeding. Material and Methods: Reduced litters of 3 mice pups and standard litters of 10 mice pups were obtained to induce overfed animals during lactation and control animals, respectively. Animals were sacrificed at 24 days (weaning) or at 7 months of life (adulthood). Body weight, blood pressure, kidney weight, and glomerular count were assessed in both groups. Senescence pathways were investigated using β-Galactosidase staining and Western blotting of P16, P21, P53, P-Rb/Rb and Sirtuin 1 proteins. Results: Early overfed animals had a higher body weight, a higher blood pressure at adulthood, and a higher glomerular number endowment compared to the control group. A higher β-Galactosidase activity, a significant increase in P53 protein expression (p=0.0045) and a significant decrease in P-Rb/Rb ratio (p= 0.02), were observed at weaning in animals who underwent early postnatal overfeeding. Protein expression of Sirtuin 1, a protective factor against accelerated stress-induced senescence, was significantly decreased (p=0.03) at weaning in early overfed animals; Conclusion: Early postnatal overfeeding by litter size reduction is associated with increased expression of factors involved in cellular senescence pathways, and decreased expression of Sirt 1 in the mouse kidney at weaning. These alterations may contribute to chronic kidney disease programming after early postnatal overfeeding.